2022
DOI: 10.35568/amu.v1i1.1833
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Training of Peer Counselors on PKPR and Post-Covid-19 AKB Socialization

Abstract: Limited knowledge of students about adolescent reproductive health is a problem that is often found in Islamic boarding school. The behavior of teenagers who often wear clothes or towels alternating with friends will be very influential for the reproductive health of adolescents, and it is feared that it could become a medium of spread of covid-19. Therefore, it is necessary to establish youth counselors and training through the provision of information as well as counseling practices on Youth Care Health Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…While there are studies indicating that school psychologists working in boarding schools frequently use peer counseling to increase students' self-esteem or enhance their coping skills (Hidayah & Sahari-Nordin, 2020;Gao et. al., 2021;Susilawati et. al., 2022), no research has been found that employs a peer counseling program for intervening in adaptation problems.…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies indicating that school psychologists working in boarding schools frequently use peer counseling to increase students' self-esteem or enhance their coping skills (Hidayah & Sahari-Nordin, 2020;Gao et. al., 2021;Susilawati et. al., 2022), no research has been found that employs a peer counseling program for intervening in adaptation problems.…”
Section: Discussionmentioning
confidence: 99%